The role of Hippo regulators in Neuropathic pain - Alameldin, Yasmin (My University, 2023)
Neuropathic pain is a major clinical challenge owing to its physiological elusiveness and lack of substantially efficient pharmacotherapies. Previously, it has been demonstrated that the Hippo pathway can be a trigger for the development of neuropathic pain, yet the mechanistic procedure of how this is achieved at the molecular level remains poorly understood. Recent studies have shed the light on Hippo-regulators, Ror2 and Wnt5A which are part of the noncanonical Wnt signalling, to be dysregulated in different models of pain. To achieve a molecular understanding of Ror2 and Wnt5A in neuropathy, expression studies at the genomic and proteomic levels were performed on the different components of the nervous system including dorsal root ganglia (DRGs), Spinal cord (Sp), brain and sciatic nerve (Sc) using the chronic constriction injury (CCI) pain model. The functional role of Wnt5A in enhancing neural excitability was explored by measuring intracellular calcium levels in dissociated sensory neurons. IMR-32 human neuroblastoma cell line was validated for future target studies by analyzing the expression profile of our targets. Herein, the expression of our targets was confirmed in the relevant tissues of the pain pathway. Ror2 immunoreactivity was found in the cell bodies of DRGs and the axonal terminals. We report increased Ror2 and Wnt5A levels in the Sc and DRGs, respectively. It was also observed that Wnt5A enhances the excitation of the sensory neurons. Finally, we were able to identify the IMR-32 cells as a suitable in vitro model for future target studies.
Keywords: neuropathic pain, Ror2, Wnt5A, CCI, IMR-32 cells, DRG, sciatic nerve